Uma história da geometria escolar no Brasil: de disciplina a conteúdo de ensino - Meneses, Ricardo Soares de (2007)
The purpose of this research is to carry out a historical study of the Geometry in the Brazil. The source of this study is mainly based on didactic books. The research is based on concepts and reflections from the cultural history. These concepts and reflections are specifically from the history of school disciplines. The present research considers the importance of authors like André Chervel, Roger Chartier and Circe Bittencourt. How would have been the way of teaching Geometry, according to the didactic books, since it became an important knowledge to the secondary school level? The results of the study indicate two essential different phases of the Geometry teaching in Brazil: The first phase refers to the period where the Geometry has become an autonomous discipline in the secondary school level, due to meet the requirement of including the Geometry concepts in the admission exams for universities The second phase refers to the period where the Geometry has become part of a regular school discipline named Mathematics. This process was started by the Francisco Campos Reform